The investigation of polyester composites filled by modified bentonite - Jastrzębska, M.; Janik, H.; Paukszta, D. (Polimery, 2014)
In this study, organically treated montmorillonite, NanoBent®ZR2 (SN), was used as a nanofiller for polyester composites containing 10, 12 or 15 wt % of glass reinforced polyester waste (W). The nanofiller was introduced to the compositions in the amount of 2 wt % of all the components. The composite matrix was unsaturated orthophthalic polyester resin (P) and dolomite dust (D) and glass reinforced polyester waste were used as a filler. The morphology of polyester/nanofiller composites (P98/SN2) and polyester composites with dolomite dust, glass reinforced waste and nanofiller were tested by means of wide angle X-ray scattering (WAXS) and scanning electron microscopy (SEM). The influence of the nanofiller on the strengths of the polyester composites was also examined. SEM studies revealed incomplete montmorillonite dispersion in the polyester matrix. After adding nanofiller to a polyester composite with 15 wt % of glass polyester waste, an increase in the compressive strength was observed. The proposed method for improving the properties of composites with glass reinforced polyester waste as a nanofiller is a new solution and to our knowledge has not been suggested so far.